Degradable starch microspheres transarterial chemoembolization (DSM-TACE) in patients with unresectable hepatocellular carcinoma: results from the Prospective Multicenter Observational HepaStar Trial - Collettini, Federico; Andrašina, Tomáš; Reimer, Peter; Schima, Wolfgang; Stroszczynski, Christian; Lamprecht, Yasmina; Auer, Timo Alexander; Rohan, Tomáš; Wildgruber, Moritz; Gebauer, Bernhard; Masthoff, Max (European radiology, 2025)
OBJECTIVES: Despite increasing interest, prospective data on the use of degradable starch microsphere-transarterial chemoembolization (DSM-TACE) in the management of patients with unresectable HCC are still scarce. The objective of the HepaStar study was to collect prospective safety and effectiveness data in a prospective multicenter observational study. MATERIALS AND METHODS: Between January 2017 and December 2022, consecutive participants with unresectable or recurrent HCC treated with DSM-TACE as standard of care at 6 participating centers in Europe were enrolled. Tumor response was evaluated according to the mRECIST criteria. Overall survival (OS), progression-free survival (PFS), and adverse events (AEs) were assessed by using Kaplan-Meier analysis and Common Terminology Criteria for Adverse Events, version 5. Liver function deterioration was assessed by monitoring changes in liver blood tests during the follow-up. RESULTS: Seventy-nine participants (median age, 69 years (IQR, 51-87 years); 67 men (85%)) were enrolled and treated. The median follow-up time was 18 months (IQR 9.5-38.0 months). The estimated median OS and PFS for the entire cohort was 32 months (CI, 95% 21-NaN) and 9 months (CI, 95% 7-NaN), respectively. Eleven (13.9%) participants experienced at least one grade 3 or 4 AE. The most frequent grade 3-4 AE was elevated bilirubin (2.2%, 5 of 79). Deterioration of bilirubin, AST, ALT, and albumin were observed in 24.1%, 23.7%, 19%, and 24% of participants, respectively. CONCLUSION: DSM-TACE achieves promising survival in patients with unresectable or recurrent HCC. This technique shows a favorable safety profile both in terms of treatment-related AEs and liver function deterioration. KEY POINTS: Question Although degradable starch microspheres transarterial chemoembolization is widely used in clinical practice across Europe, prospective data on its application in hepatocellular carcinoma patients remains limited. Findings Degradable starch microspheres transarterial chemoembolization results in promising survival rates, good tumor response rates, and low rates of treatment-related adverse events. Clinical relevance In patients with unresectable hepatocellular carcinoma, degradable starch microspheres transarterial chemoembolization represents a safe and effective alternative to more well-established chemoembolization techniques like conventional transarterial chemoembolization and drug-eluting beads transarterial chemoembolization.
Keywords: výsledek terapie; škrob; Male; Microspheres; Chemoembolization, Therapeutic; Liver cancer; Carcinoma, Hepatocellular; Aged; Prospective Studies; mužské pohlaví; senioři; Chemoembolization; Hepatocellular carcinoma; Embolization; Treatment Outcome; mikrosféry; senioři nad 80 let; lidé; ženské pohlaví; nádory jater; Humans; hepatocelulární karcinom; Aged, 80 and over; chemoembolizace; Starch; Liver Neoplasms; Female; lidé středního věku; Middle Aged; prospektivní studie